The Use of Proton Pump Inhibitors Among Older Adults with Intellectual Disability: A Cross Sectional Observational Study. - Henman, Martin; ALMUTAIRI, HADIAH KHALAF; O'Dwyer, Maire; Mc Carron, Mary; McCallion, Philip (My University, 2018)
Background: Older people with Intellectual Disability (ID) have a high prevalence of gastrointestinal conditions such as Gastro-Oesophageal Reflux Disease (GORD). However, despite this, information about treatment, in particular the use of Proton Pump Inhibitors (PPIs), in this population is sparse and limited. Objective: To investigate the prevalence and pattern of PPI use among older people with ID. Method: Data on PPI use and key demographics was analysed from Wave 2 (2013/2014) of IDS-TILDA, a nationally representative longitudinal study of 677 participants aged 40 years and above in Ireland. Descriptive statistics, bivariate analyses and binary logistic regression were carried out. Results: Just over a quarter, 27.9% (n = 189), of participants reported use of PPIs, and 53.4% (n = 101) were female. The largest proportion of PPI users (53.4%) were aged between 50 and 64 yrs. Most of the PPIs were used in maximum doses (66.7%). However only 43.9% of PPI users had an indication for PPI use (GORD, stomach ulcer or/and an NSAID use), and further 13.2% were also taking an antiplatelet agent. Use among those in residential care homes (54.3%) was much higher than for those living independently or with family (7%). PPI use among those who have severe/profound ID was 25% higher than those with mild ID. Information about the length of PPI use was missing for 31.2%, but of those with data, just over half recorded using the PPIs for more than a year. Apart from an indication, the factors associated with PPI use were older ages (over 50 years), severe/profound level of ID. Conclusion: PPI use among older people with intellectual disability is prevalent and frequently long term, often without a clear indication. PPI use especially among those with severe/profound ID and those who live in residential care homes, could predispose these individuals to additional comorbidities and in order to avoid inappropriate long term of use regular review is required.
Keywords: Older people; Intellectual disability; Proton pump inhibitors; Medicine use; Inappropriate; Polypharmacy; Medication; Peptic ulcer disease; Ageing; ACID REFLUX; ANTIULCER AGENT; Ageing & Intellectual Disability - Changing Service Needs; Ageing & Intellectual Disability Issues; Ageing, Health and Intellectual Disability; Aging and Intellectual Disability; Clinical Pharmacy; GASTRIC ULCER; GASTRO-OESOPHAGEAL REFLUX; GASTRO-OESOPHAGEAL REFLUX DISEASE; Gastroenterology; INTELLECTUAL DISABILITIES; Intellectual Disability; NONULCER DYSPEPSIA; Older people with intellectual disabilities; PEPTIC ULCER; PEPTIC-ULCER DISEASE; PHARMACOEPIDEMIOLOGY; PHARMACY PRACTICE; POLYPHARMACY; PRESCRIBING; PRESCRIBING PATTERNS; PROTON PUMP INHIBITOR; Patient safety; Practice of pharmacy; QUALITY PRESCRIBING; RATIONAL PRESCRIBING; REFLUX ESOPHAGITIS; SYMPTOMATIC GASTROESOPHAGEAL REFLUX